2008
DOI: 10.1177/0265659007084569
|View full text |Cite
|
Sign up to set email alerts
|

Interview stories: Early years practitioners' experiences with children with speech, language and communication needs

Abstract: Interviews were conducted with 50 early years practitioners, exploring their experiences with children with speech, language and communication needs (SLCN). A narrative approach was taken to elicit information on the children they were working with who had these needs. This included characteristics of the children's behaviour, how they were identified and strategies used to help them. Participants identified children to discuss, many of whom had complex needs. There was large variation in how the children were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…The findings of this study are consistent with previous research that has shown that ECEs in childcare contexts have knowledge and skill in their work with young children, providing educational opportunities, not only care of basic needs (Brebner et al, 2015; Elfer and Page, 2015; Mroz and Letts, 2008). The ECEs who participated in this study demonstrated their knowledge and application of early communication development.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The findings of this study are consistent with previous research that has shown that ECEs in childcare contexts have knowledge and skill in their work with young children, providing educational opportunities, not only care of basic needs (Brebner et al, 2015; Elfer and Page, 2015; Mroz and Letts, 2008). The ECEs who participated in this study demonstrated their knowledge and application of early communication development.…”
Section: Discussionsupporting
confidence: 91%
“…Childcare can provide rich learning experiences and support the development of young children’s foundational skills (Gialamas et al, 2015; Gibbard and Smith, 2016; McCartney et al, 2007; Mustard, 2008; Speech Pathology Australia, 2014). It also provides an opportunity for early identification of those at risk or vulnerable in their development, when early intervention can be effective in mitigating long-term consequences (Mroz and Letts, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence suggests that many parents and practitioners are unsure of when and if to seek help if they think a child has difficulty (Talk to Your Baby 2005; Mroz and Letts 2008;Prelock et al 2008). Rescorla and Ratner (1996) determine that a two-year-old child with a vocabulary of less than fifty words and some two word combinations has a language difficulty.…”
Section: The Complexities Of Identifying Language Difficultiesmentioning
confidence: 99%
“…Furthermore, such training tended to cover typical language development rather than language delays/disorders and was mostly not administered by specialist tutors (Letts and Hall, 2003). Letts and Hall (2003) reported that staff members who referred children due to suspected SLCN were not necessarily those who were more senior and/or who had received appropriate training (Mroz and Letts, 2008). Mroz and Hall (2003) carried out an additional measure with the 829 EYPs, requiring them to decide whether to refer three 'case study' scenarios.…”
Section: Introductionmentioning
confidence: 99%